2007
DOI: 10.1177/0033688206076155
|View full text |Cite
|
Sign up to set email alerts
|

English as a Global Language

Abstract: The argument put forward here is that we are witnessing the emergence of a concept of English as a lingua franca, which creates a set of attitudes about correctness and in particular ‘grammatical correctness’. The traditional ‘nativespeaker’ as final arbiter can only apply to English as a national language. It is the non-native speaker who is becoming the model for English as a global language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…However, English is in practice the de facto L2 and used in a wide range of domains including its use as the main, although not only, lingua franca of communication in regional and global contexts. Thailand is thus often categorised as an ELF environment (Foley, 2007;Kirkpatrick, 2007;Taylor, 2006). English is a compulsory L2 in schools and in tertiary education and the most popular foreign language learned in school and in private tuition classes (Wongsothorn Sukamolsun, Chinthammit, Ratanothayanonth, & Noparumpa, 1996, pp.…”
Section: Intercultural Communication In Thailand: a Study Of Elf In Pmentioning
confidence: 99%
“…However, English is in practice the de facto L2 and used in a wide range of domains including its use as the main, although not only, lingua franca of communication in regional and global contexts. Thailand is thus often categorised as an ELF environment (Foley, 2007;Kirkpatrick, 2007;Taylor, 2006). English is a compulsory L2 in schools and in tertiary education and the most popular foreign language learned in school and in private tuition classes (Wongsothorn Sukamolsun, Chinthammit, Ratanothayanonth, & Noparumpa, 1996, pp.…”
Section: Intercultural Communication In Thailand: a Study Of Elf In Pmentioning
confidence: 99%
“…As Crystal (2006) points out that the estimated number of people who use English as their second language is 430 million while the number of people who use English as their first language is 330 million, excluding the number of learners which might approximately be one billion learners of English (cited in Deterding and Kirkpatrick , 2006). Moreover, Kachru states that a survey conducted by the India Today magazine found that 333 million people in India use English every day in their life which means that out of three people in India one uses English daily (cited in Foley, 2007). The people who use English as their second language do not isolate their cultures from the language but bring their cultures to the scene and adjust the language, or in other words localize English to suit their own cultures and societies.…”
Section: The Spread Of English Languagementioning
confidence: 99%
“…The people who use English as their second language do not isolate their cultures from the language but bring their cultures to the scene and adjust the language, or in other words localize English to suit their own cultures and societies. Foley (2007) points out that languages change according to the way people use it and in the case of English, which is used globally, it is shaped by its non-native speakers as by its native speakers. English has gained considerable influence not only among post-colonial societies but also among most other international societies.…”
Section: The Spread Of English Languagementioning
confidence: 99%
See 1 more Smart Citation
“…The fact that English has become a global language (Crystal, 2003;Foley, 2007;Nunan, 2001Nunan, , 2003 has originated an increasing interest on the use of Communicative Language Teaching (CLT) in the English as a Foreign Language (EFL) classroom. However, it is easy to observe a lack of correspondence between CLT approach and what is really taught in the EFL classroom.…”
Section: Introductionmentioning
confidence: 99%